Comparison of the amino acid sequences of the variable regions of light chains derived from two homogeneous rabbit anti-pneumococcal antibodies - Jaton, Jean-Claude (1974)
The amino acid sequence of the N-terminal 139 residues of the L (light) chain derived from a homogeneous rabbit antibody to type III pneumococci was determined. This L chain, designated BS-5, exhibits a greater degree of homology with the basic sequence of human κ chains of subgroup I (72%) than with subgroups II and III. L-chain BS-5 differs from another L chain (BS-1), also derived from an antibody to type III pneumococci (Jaton, 1974), by eight amino acid residues, even though the chains are identical within the N-terminal 30 residues. Six of these eight substitutions are located within the three hypervariable sections of the variable half: Asn/Ser in position 31, Glu/Ala in position 55, Asx/Thr, Thr/Gly, Thr/Gly and Val/Tyr in positions 92, 94, 96 and 97 respectively. The two anti-pneumococcal L chains BS-1 and BS-5 are much more similar to each other than to an anti-azobenzoate L chain (Appella et al., 1973), from which they differ by 30 and 29 residues respectively. Of these interchanges 13–15 are confined to the three hypervariable sections, and 11 occur within the N-terminal 27 positions. The three chains have an identical sequence from residue 98 to residue 139, except for a possible inversion of two residues in positions 130–131 of the anti-azobenzoate chain.